Developing intercultural perspectives on language use : exploring pragmatics and culture in foreign language learning - McConachy, Troy, 1980- (Bristol ; Blue Ridge Summit : Multilingual Matters, 2018)
'Many teachers recognise the importance of integrating intercultural learning into language learning. This book argues that teachers can work creatively with conventional resources and utilise classroom experiences in order to help learners develop awareness of the influence of cultural assumptions and values on language use' --
Pragmatics and culture in communicative language teaching -- Linking pragmatics and intercultural language learning -- Developing a view of language use as social action -- Reflection on experience as resource for intercultural learning -- Combining performance and reflection for learning -- Developing intercultural perspectives on language use.
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching; Intercultural communication -- Study and teaching; Language and culture -- Study and teaching; Multicultural education